Effect of cerebrospinal fluid drainage on clinical outcomes following aneurysmal subarachnoid hemorrhage. (March 2022) - Ascanio, Luis C.; Gupta, Raghav; Tachie-Baffour, Yaw; Chida, Kohei; Dmytriw, Adam A.; Enriquez-Marulanda, Alejandro; Chinnadurai, Anu; Alturki, Abdulrahman Y.; Ogilvy, Christopher S.; Thomas, Ajith J.; Moore, Justin M.
Highlights: The relationship between the EVD output and clinical outcomes in aneurysmal subarachnoid hemorrhage patients is unknown. An increased EVD output was associated with improved functional outcomes at last clinical follow-up when adjusted for potential confounders. EVDs set at 10 cmH2 O with output close to 200 ml predicted a 50% probability of good outcomes. An increased EVD output was associated with less incidence of clinical and radiographic vasospasm. Abstract: Objectives: We study the relationship between external ventricular drainage (EVD) of cerebrospinal fluid output and functional outcomes in patients with aneurysmal subarachnoid hemorrhage (aSAH). Methods: A retrospective chart review of patients presenting to a single center with aSAH was performed. The primary outcome was good functional outcomes assessed by a composite of the modified Rankin scale (mRS 0–2) at last follow-up. Secondary outcomes were clinical and radiographic vasospasm. For data analysis, multivariable generalized estimating equations adjusting for potential confounders were used. Results: A total of 119 patients were included; 91 (75.6%) presented with a modified Fisher grade 4 and 76 (63.9%) had hydrocephalus. The median EVD duration was 13 days. On average, most EVDs were set at 15 cmH2 O (50, 42%). Follow-up was available in 109 patients; median time was 10.7 months; 69 (63.3%) had good outcomes. Multivariable analysis showed that EVDs set at 10 cmH2 O had increased odds of good outcomes for every ml increase in the EVD output (OR = 1.02; 95% CI 1.01–1.03; p = 0.001). Post estimation analyses show that EVDs at 10 cmH2 O with output close to 200 ml predicted a 50% probability of good outcomes. Conclusions: Increased EVD outputs were associated with favorable outcomes at the last follow-up.